Evaluation of the electrical rates scheme in Peru based on cases sanctioned by the regulatory bodyALUACIÓ (Dissertare, 2020)
This article assesses the rate scheme of the Peruvian electricity service in terms of compliance with the regulatory framework for its provision by regulated companies. To do this, 27 files of sanctions imposed by the Supervisory Agency for Investment in Energy and Mining (acronym in Spanish: OSINERGMIN) to various nationally regulated electricity companies between 2013 and 2015 are analyzed. The work approach is quantitative, descriptive, with a documentary design and application of bibliographic review techniques in data collection. The treatment of these was based on the application of descriptive statistics, through the analysis of frequencies. The results of the study show that the sanctions imposed by the regulatory body in the analyzed period were due to four types of non-compliance: lack of quality in the service, information asymmetric, disconnection of the service, lack of maintenance, with a significant representation of this last type of transgression, in which several companies were repeat offenders. The study concludes that the rate scheme of the Peruvian electricity system has not succeeded in ensuring that regulated companies provide a service adjusted to the regulatory framework and quality requirements in its provision.
Keywords: regulation; electricity service; public services; concessions